2021
DOI: 10.1002/glia.24111
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes in central nervous system remyelination

Abstract: Remyelination failure with aging and progression of neurodegenerative disorders contributes to axonal dysfunction, highlighting the importance of understanding the mechanisms underpinning this process to develop regenerative therapies. Central nervous system (CNS) macrophages, encompassing both resident microglia and blood monocyte-derived cells, play a crucial role in driving successful remyelination.Although there has been a focus on the critical roles of microglia in remyelination, the specific contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Microglia communicate extensively with other cells through direct cellular interactions, ligand‐receptor interactions and extracellular vesicles. Harmonious intercellular communication involving microglia is important to maintain a healthy state of the tissue environment and to overcome pathology including neuroinflammation (Borst et al, 2021 ; Forbes & Miron, 2021 ; Ronzano et al, 2021 ). Our FACS analysis indicated that, during remission, the majority of myeloid and T cells that infiltrated from the periphery in the acute stage had been cleared from the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia communicate extensively with other cells through direct cellular interactions, ligand‐receptor interactions and extracellular vesicles. Harmonious intercellular communication involving microglia is important to maintain a healthy state of the tissue environment and to overcome pathology including neuroinflammation (Borst et al, 2021 ; Forbes & Miron, 2021 ; Ronzano et al, 2021 ). Our FACS analysis indicated that, during remission, the majority of myeloid and T cells that infiltrated from the periphery in the acute stage had been cleared from the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…After injury, microglia acquire an activated, more phagocytic phenotype in response to cues from the environment (Keren‐Shaul et al, 2017 ; Krasemann et al, 2017 ; Kreutzberg, 1996 ). In MS, macrophages, including microglia, phagocytose myelin debris, modulate the extracellular matrix and secrete regenerative factors in order to create a favorable environment for oligodendrocyte progenitor cell (OPC) recruitment and OPC maturation, and therefore are relevant to remyelination (Forbes & Miron, 2021 ; Kotter et al, 2006 ; Lampron et al, 2015 ; Lloyd & Miron, 2019 ; Robinson & Miller, 1999 ). However, the extent to which microglia contribute to initiation and repair of MS lesions, especially in the secondary‐progressive phase has been poorly defined (Geladaris et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia, peripheral monocytes/macrophages, and other innate immune cell types can both induce and resolve inflammation [ 23 , 24 ]. In the central nervous system (CNS), resident (microglia) and infiltrating innate immune cells coordinate a complex response toward the tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Myeloid cells are abundant in MS lesions and perivascular infiltrates 1,3 . Blood monocytes infiltrating the CNS and then differentiating into macrophages, coined monocyte‐derived macrophages (MDMs), represent the majority of myeloid cells detected in MS lesions 4 . Macrophages and microglia shape the inflammatory milieu of the CNS via the production of numerous molecules 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Blood monocytes infiltrating the CNS and then differentiating into macrophages, coined monocytederived macrophages (MDMs), represent the majority of myeloid cells detected in MS lesions. 4 Macrophages and microglia shape the inflammatory milieu of the CNS via the production of numerous molecules. 1,3 The characterization of these factors and the identification of the mechanisms driving their expression shed light on the plasticity and the large spectrum of phenotypes and functions myeloid cells possess (i.e.…”
Section: Introductionmentioning
confidence: 99%